Präzisierung der Konstitution der Sulfonierungsprodukte von o-Toluidin - Alfred Courtin; Kurt Brenneisen (CHIMIA)
Sulfonation of o-toluidine (1) in oleum yields only 2-amino- toluene-4-sulfonic acid (4), while the isomeric 2-aminotoluene- 5-sulfonic acid (2) can be prepared solely by baking the acid sulfate salt of 1. Further sulfonation of 4 afforded 2-amino- toluene-4,5-disulfonic acid (6) whose structure was proven by deamination to toluene-3,4-disulfonic acid (8). The latter was independently synthesized from 4-aminotoluene-3-sulfonic acid (7) by successive treatment with potassium ethyl xanthate, hydrolysis and oxidation.